Positive Association Between Serum Alkaline Phosphatase and First Stroke in Hypertensive Adults - Zhang, Yuanyuan; Li, Huan; Xie, Di; Li, Jianping; Zhang, Yan; Wang, Binyan; Liu, Chengzhang; Song, Yun; Wang, Xiaobin; Huo, Yong; Hou, Fan Fan; Xu, Xiping; et al. (Frontiers in Cardiovascular Medicine, 2021)
The relation of alkaline phosphatase (ALP) with stroke risk remains uncertain. We aimed to examine the association between serum ALP and the risk of first stroke, and explore the possible effect modifiers in the association, among adults with hypertension. A total of 19,747 participants with baseline ALP measurements and without liver disease at baseline from the China Stroke Primary Prevention Trial (CSPPT) were included. The primary outcome was a first stroke. Over a median follow-up of 4.5 years, there was a positive association between serum ALP levels and the risk of first stroke (per SD increment, adjusted HR, 1.10; 95%CI: 1.01, 1.20). When serum ALP was evaluated as quartiles, a significantly higher risk of first stroke was observed in those in quartile 2–4 (ALP ≥79 IU/L; adjusted HR, 1.38; 95% CI: 1.11, 1.71), compared with participants in quartile 1 (ALP <79 IU/L). Similar results were found for first ischemic or hemorrhagic stroke. Similar findings were also found in those with a normal range of baseline ALP levels (20–140 IU/L) (per SD increment, adjusted HR, 1.15; 95%CI: 1.05, 1.27). None of the variables, including sex, age, body mass index, smoking, alcohol drinking, blood pressure, total cholesterol, fasting glucose levels at baseline, and blood pressure levels during the treatment period, significantly modified the association. In summary, our study suggests that higher serum ALP levels, even in normal range, were significantly related to higher risk of first stroke among Chinese hypertensive adults.